Public Service Complaints Through Electronic Communication Media in The Era Of Digital Democracy in South Sumatera Province: Political and Public Policy Analysis - Septiana Wulandari; Umi Rahmawati; Merita Auli; Tatang Sudrajat (Public Service and Governance Journal, 2025)
The development of communication and information technology currently has a major impact on the pattern of public complaints about public services which in the era of digital democracy are inseparable from the dynamics of regional government. The presence of regulations regarding public services through Law Number 25 of 2009 and various derivative regulations in the implementation of regional government is an important part of moving towards a more democratic life. This study aims to discuss the policy of the South Sumatera Provincial Government in handling public service complaints through electronic communication media in the era of digital democracy from a political and public policy perspective. The study uses a combination of normative legal methods and secondary data analysis. The study concludes that politically, handling public complaints about regional government services is a positive thing. In the context of digital democracy and the quality of public services, the response of the regional government to public complaints is a measure of good governance. The issuance of Regional Regulation Number 3 of 2013, Governor Regulation Number 26 of 2016, and Governor Regulation Number 9 of 2022 are concrete manifestations of public policy. As a product of the political process, this is substantively related to public services and public complaints in the digital era. The existence of an electronic complaint channel regarding public services opens up space for increasing public awareness of their rights. Political life will be more democratic when communication between the government and the people runs functionally. There are several regional policy substances that need to be improved.